Pomalidomide - An appraisal of its clinical development and role in the treatment of relapsed/refractory multiple myeloma - Richardson, P.G.; Palumbo, A.; Schey, S.A.; Dimopoulos, M.A.; Facon, T.; Weisel, K.C.; O'Gorman, P.; Leleu, X.; Lacy, M.Q.; Streetly, M.J.; Mikhael, J.R.; Siegel, D.S.; et al. (European Oncology and Haematology, 2015)
Pomalidomide is a distinct immunomodulatory agent with significant activity in relapsed/refractory multiple myeloma (RRMM). The optimal treatment schedule in patients with RRMM who have received multiple lines of treatment, including bortezomib and lenalidomide, is 4 mg/day on days 1-21 of a 28-day cycle in combination with weekly low-dose dexamethasone. Improved responses and outcomes relative to traditional therapies continue to be confirmed in recently completed and ongoing trials. Pomalidomide exhibits direct tumoricidal, immunomodulatory, anti-angiogenic and anti-inflammatory activities, which facilitate combination therapy with agents with complementary mechanisms of action, resulting in greater anti-myeloma effects than single-agent therapy or previous combination therapies. For example, in combination with proteasome inhibitors and traditional chemotherapeutic agents in doublet or triplet regimens, pomalidomide provides high rates of durable response, and represents an important new treatment option for patients with RRMM requiring effective new therapies. Additionally, pomalidomide maintains its efficacy and tolerability profile in difficult-to-treat patients, including the elderly, patients with poor cytogenetics and those with renal impairment. This review summarises the clinical development of pomalidomide and discusses this effective agent for the treatment of patients with RRMM in the context of current myeloma treatment options, as well as potential future directions to further improve patient outcomes.
Keywords: IMiD; Immunomodulatory agent; Lenalidomide; pomalidomide; relapsed/refractory multiple myeloma; Treatment-resistant multiple myeloma